2023
DOI: 10.1002/joc.8159
|View full text |Cite
|
Sign up to set email alerts
|

Changes of mean and extreme precipitation and their relationship in Northern Hemisphere land monsoon domain under global warming

Yeyan Jiang,
Zhiwei Zhu,
Juan Li
et al.

Abstract: Reliable projections of monsoon mean and extreme precipitation are vital to water resource management, disaster mitigation as well as policy makings. Since the climate models have better capability in projecting mean precipitation, the relationship between mean and extreme precipitation is a crucial clue for reliable projections of extreme precipitation. However, selections of optimal models in reproducing historical mean/extreme precipitation and their relationship were rarely reported. Here, more credible pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Models from the sixth phase of Coupled Model Intercomparison Project (CMIP6; Eyring et al., 2016) are primary tools to project future changes in extreme rainfall, but the credibility remains uncertain (Jiang et al., 2023; C. Li, Zwiers, et al., 2021; F. Li et al., 2022; H. Xu et al., 2021). Here we found that CMIP6 models generally projected increased extreme rainfall frequency over MLYR (see definition in Section 2.2.1) under two Shared Socioeconomic Pathways (SSP; i.e., SSP3‐7.0 and SSP5‐8.5; O'Neill et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Models from the sixth phase of Coupled Model Intercomparison Project (CMIP6; Eyring et al., 2016) are primary tools to project future changes in extreme rainfall, but the credibility remains uncertain (Jiang et al., 2023; C. Li, Zwiers, et al., 2021; F. Li et al., 2022; H. Xu et al., 2021). Here we found that CMIP6 models generally projected increased extreme rainfall frequency over MLYR (see definition in Section 2.2.1) under two Shared Socioeconomic Pathways (SSP; i.e., SSP3‐7.0 and SSP5‐8.5; O'Neill et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Models from the sixth phase of Coupled Model Intercomparison Project (CMIP6; Eyring et al, 2016) are primary tools to project future changes in extreme rainfall, but the credibility remains uncertain (Jiang et al, 2023;C. Li, Zwiers, et al, 2021;F.…”
mentioning
confidence: 99%